2022
DOI: 10.1101/2022.10.19.512888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping genetic variants for nonsense-mediated mRNA decay regulation across human tissues

Abstract: Background: Nonsense-mediated mRNA decay (NMD) was originally conceived as an mRNA surveillance mechanism to prevent the production of potentially deleterious truncated proteins. Recent research shows NMD is an important post-transcriptional gene regulation mechanism selectively targeting many non-aberrant mRNAs. However, how natural genetic variants affect NMD and modulate gene expressions remains elusive. Results: Here we elucidate NMD regulation of individual genes across human tissues through genetical gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…We also identified genes whose mechanistic links to NMD are less obvious; replication in additional cohorts would be the sensible next step. A recent study identified genetic variants that influence NMD-targeted transcripts and their NMD decay efficiency across healthy GTex tissues 106 , with more than 50% of NMD-QTLs identified in the brain in particular. Interestingly, SF3B4, one of our identified candidates from somatic associations, emerged as the gene containing the highest number of germline NMD-QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified genes whose mechanistic links to NMD are less obvious; replication in additional cohorts would be the sensible next step. A recent study identified genetic variants that influence NMD-targeted transcripts and their NMD decay efficiency across healthy GTex tissues 106 , with more than 50% of NMD-QTLs identified in the brain in particular. Interestingly, SF3B4, one of our identified candidates from somatic associations, emerged as the gene containing the highest number of germline NMD-QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that abnormal mRNA containing premature stop codons could be recognized and degraded by nonsense-mediated mRNA decay (NMD). NMD is an important RNA surveillance mechanism in eukaryotic cells to avoid cell toxicity caused by the accumulation of truncated protein products [33]. As an intracellular mRNA monitoring mechanism, NMD protects the body from damage by nonsense IRAK4 protein.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, recent studies [62][63][64][65] have found that approximately half of GWAS loci that share a causal variant (colocalize) with splicing quantitative trait loci (sQTLs) also colocalize with an eQTL, suggesting that the impact of AS is often mediated by gene expression levels rather than alternate protein isoforms. However, the overlap of sQTLs, eQTLs, and GWAS does not immediately imply AS-NMD mechanisms because alternative promoters, isoform-specific mRNA decay, and other molecular processes can similarly affect both expression and splicing measurements [52][53][54][55] . To better resolve how these sQTLs may be functioning, we compiled summary statistics from 45 GWAS for blood and immune-related traits and evaluated the enrichment of GWAS signal among various classes of molecular QTLs: eQTLs, H3K27Ac QTLs, p-sQTLs, and u-sQTLs For example, using multiple sclerosis GWAS summary statistics, we find enrichment of u-sQTLs on par with that of p-sQTLs, hQTLs, and eQTLs (Figure 4A).…”
Section: Phenotypic Impact Of As-nmdmentioning
confidence: 99%
“…However, we and others have noted that alternative transcription initiation or polyadenylation can alter splicing quantifications, and vice versa 32,[44][45][46] . Furthermore, preferential decay of specific mRNA isoforms may manifest as sQTL-eQTL colocalizations 47 , without being mediated by AS. To better assess whether splicing changes causally drive the observed abundance of eQTL-sQTL colocalizations, we interrogated the genetic variants underlying post-transcriptional eQTLs.…”
Section: Pervasive Effects Of Sqtls On Gene Expression Levelsmentioning
confidence: 99%